Siyaq al-Kalam sebagai Kunci Nuansa Makna dalam Al-Qur'an: Studi Semantik Kontekstual - Alifia Nur Rizkilah; Bashori Bashori (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study explores the crucial role of Siyaq al-Kalam in uncovering the nuances of meaning in the Qur’anic verses using a contextual semantic approach. The research employs qualitative methods through library research to analyze how linguistic, thematic, and historical contexts enrich the understanding of Qur’anic texts. The findings indicate that Siyaq al-Kalam—comprising linguistic, thematic, and situational contexts—plays a central role in preventing misinterpretation and in achieving a more authentic understanding of the Qur’an’s messages. This study confirms and deepens existing contextual semantic theories and contributes to the development of Qur’anic linguistic studies. Nevertheless, this research remains descriptive and requires further empirical studies to validate and expand its findings. It is therefore recommended that future studies incorporate field-based approaches and practical applications, so that the theoretical insights of Siyaq al-Kalam can be more effectively implemented in educational and interpretative practices of the Qur’an.